Effects of pH and metal ions on oxytetracycline sorption to maize-straw-derived biochar - Jia, Mingyun; Wang, Fang; Bian, Yongrong; Jin, Xin; Song, Yang; Kengara, Fredrick Orori; Xu, Renkou; Jiang, Xin (Bioresource technology, 2013)
► Oxytetracycline (OTC) sorbed to biochar according to pseudo-second-order kinetics. ► OTC sorption increased with increasing pH but decreased at high pH values. ► Zwitterions are the most sorbed oxytetracycline species on biochar. ► Cu2+ strongly enhances the sorption of OTC to biochar through metal bridging. ► π–π interactions and metal bridging were the main OTC-biochar sorption mechanisms. Biochars produced from biomass residues have been recognized as effective sorbents to hydrophobic compounds, but knowledge on sorption of antibiotics to biochar and its mechanisms are still inadequate. Sorption of oxytetracycline (OTC) in aqueous solution to maize-straw-derived biochar, and the effect of pH and metal ions, was investigated in batch experiments, and the main sorption mechanisms were elucidated using FTIR and zeta potential measurements. The results showed that sorption of OTC on biochar was highly pH-dependant. The amount of sorbed OTC first increased and then decreased with increasing pH, and maximum sorption was achieved at pH 5.5. Cu2+ enhanced the sorption of OTC, while Pb2+ slightly reduced the sorption under acidic conditions. Other metal ions had no significant effect on the sorption of OTC to biochar. Surface complexation, through π–π interaction and metal bridging, was the most important sorption mechanism although cation exchange might have played a role.